2021
DOI: 10.3390/app11052200
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamics of Cycling Skinsuits Focused on the Surface Shape of the Arms

Abstract: In cycling, air resistance corresponds to 90% of the resistance on the bicycle and cyclist and 70% of this is applied to the body of the cyclist. Despite research on postures that could reduce air resistance, few studies have been conducted on full-body cycling suits. As the aerodynamics of the surface shape of clothing fabric are still unclear, the airflow around cyclists and air resistance were examined using a computational fluid dynamics (CFD) method and wind tunnel experiment. Specifically, in this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In order to evaluate the influence of the field wind environment on cross-country skiing athletes' performance, the first step is to obtain the wind-induced aerodynamic drag of the athletes in the ski field wind environment. In recent years, many researchers have carried out research work on the acquisition of athletes' wind-induced aerodynamic drag through numerical calculation methods based on computational fluid dynamics (CFD) and wind tunnel experiments [6][7][8][9]. Chen [10] used steady and unsteady models to simulate 2D athlete models, and the results indicated that wind and posture affect the aerodynamic performance of a skier during the flight stage.…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the influence of the field wind environment on cross-country skiing athletes' performance, the first step is to obtain the wind-induced aerodynamic drag of the athletes in the ski field wind environment. In recent years, many researchers have carried out research work on the acquisition of athletes' wind-induced aerodynamic drag through numerical calculation methods based on computational fluid dynamics (CFD) and wind tunnel experiments [6][7][8][9]. Chen [10] used steady and unsteady models to simulate 2D athlete models, and the results indicated that wind and posture affect the aerodynamic performance of a skier during the flight stage.…”
Section: Introductionmentioning
confidence: 99%
“…As an indispensable piece of equipment in most sports, the drag-reducing effects of clothing has been proven in many sports. 5,6 Therefore, understanding the aerodynamic characteristic of fabrics is of great help to improve the athletes’ performance.…”
Section: Introductionmentioning
confidence: 99%
“…Many sports have proved the drag-reducing effects of clothing as an indispensable piece of equipment. 13 As a result, understanding the aerodynamic behavior of sports garments can increase efficiency and achievement. From prior studies, it is clear that despite the complex structure of the human body, human body parts can be represented as multiple cylinders for aerodynamic evaluation in wind tunnel experimentation.…”
mentioning
confidence: 99%